Stability of Sodium Pentobarbital 5w/v% Aqueous Solution During Short‐Term Chilled and Ambient‐Temperature Storage - Masakazu Dohi; Kayoko Ueda; Yoshinori Yamagiwa; Atsuko Yamashita; Yuji Sakamoto (Veterinary Medicine and Science)
ABSTRACT The COVID‐19 pandemic made it difficult to obtain pharmaceutical‐grade injectable anaesthetics used in animal experiments in Japan. To address this problem, it is worth the effort to evaluate whether the use of non‐pharmaceutical‐grade sodium pentobarbital (PBNa) water solution can be an alternative one from the perspective of stability, physicochemical properties, bioavailability and so on. In this article, as a first step, we examined the stability of PBNa 5w/v% aqueous solution (PBNa 5% AS). PBNa 5% AS sample was prepared simply by dissolving non‐pharmaceutical‐grade PBNa into water and was stored at 25°C and 5°C for 15 days. Visual appearance, pH, osmolality and assay (contents of PBNa and related substances) were tested. The stability test results indicated that there was no profound change in these test items of the PBNa 5% AS under either storage condition, suggesting that the formulation was sufficiently stable in such a short term. The only observable change was an increase of an impurity under 25°C storage; however, it was at a negligible level. Moreover, as the pH of the formulation remained <10.0 throughout the storage period in both conditions, the irritant level of the pH is considered to be acceptable. Therefore, from the viewpoint of the stability and physicochemical properties, PBNa 5% AS can be an alternative injectable anaesthetic when access to pharmaceutical‐grade anaesthetics is limited, as long as used in short‐term from its preparation.